Robot-assisted thoracic surgery in Colombia: a multi-institutional initial experience (2019)
Background: Robotic assisted videothoracoscopic surgery (RVATS) adoption has increased worldwide from 3.4% in 2010 to 17.5% in 2015. However, in Latin America, the literature is limited to a report of a series of 10 patients who underwent RVATS lobectomy and one case report of an RVATS thymectomy from Brazil. Methods: This is a retrospective review of all RVATS performed in Bogotá Colombia since 2012. A single thoracic surgeon (RB) performed all the operations at three institutions: Clínica de Marly, Fundación Clínica Shaio and Instituto Nacional de Cancerología. Preoperative, intraoperative, postoperative and pathology report variables were included. Patients were analyzed in three groups: robotic RVATS pulmonary resections, RVATS mediastinal surgeries and other RVATS procedures. Descriptive statistics were used to report the median and interquartile range (IQR) of the continuous variables, and number and percentage were used to describe categorical variables. The association between total operative time and the year the surgery was analyzed using a linear regression model. Results: Forty-seven patients underwent RVATS pulmonary resections; 72.3% (n=34) of these patients underwent a RVATS lobectomy. The median total operative time was 220 (IQR: 200 to 250) minutes, 6.4% (n=3) had intraoperative complications, and the most frequent histologic diagnosis was adenocarcinoma (n=24, 51.1%). Of 18 patients who underwent RVATS mediastinal surgeries, 50.0% (n=9) had RVATS thymectomy, the median total operative time was 195.5 (IQR: 131 to 221) minutes and two patients (11.1%) had intraoperative complications. The linear regression model of the association between total operative time and the year the surgery showed a 10.3 minute reduction per year (P=0.006). Conclusions: This is the second series of RVATS published in Latin America and the first published in Colombia, with comparable perioperative results to other reports.